The Novel Long QT Syndrome Type 2-associated F129I Mutation in the KCNH2 Gene Significantly Affects IKr Through the hERG1 Homomeric and Heteromeric Potassium Channels - Li Feng; Kejuan Ma; Xin Li; Nian Liu; Deyong Long; Changsheng Ma (Cardiology Discovery)
Objective:. The long QT syndrome type 2 is caused by the loss-of-function mutations in the KCNH2 gene, which encodes hERG1, the voltage-gated potassium channel. The hERG1 channels conduct rapid delayed rectifier K+ currents (IKr) in the human cardiac tissue. KCNH2 encodes 2 main isoforms—hERG1a and hERG1b, which assemble to form the homomeric or heteromeric hERG1 channels. However, the functional characteristics of the heteromeric hERG1 channels in long QT syndrome type 2 are not clear. In this study, a novel mutation in the N-terminus of hERG1a (F129I) was identified in a proband of long QT syndrome type 2. The purpose of this study was to identify the electrophysiological change of homomeric and heteromeric hERG1 channels with the F129I-hERG1a. Methods:. Candidate genes were screened by direct sequencing. F129I-hERG1a was cloned in the pcDNA3.1 vector by site-directed mutagenesis. Then, the wild-type (WT) hERG1a and/or F129I-hERG1a were transiently expressed in the HEK293 cells with or without hERG1b co-expression. The expression levels of the transgenes, cellular distribution of hERG1a and hERG1b, and the electrophysiological features of the homomeric and the heteromeric hERG1 channels with the WT-hERG1a or F129I-hERG1a were analyzed using whole-cell patch-clamp electrophysiology, western blotting, and immunofluorescence techniques. Results:. The proband was clinically diagnosed with long QT syndrome type 2 and carried a heterozygous mutation c.385T>A (F129I) in the KCNH2 gene. Electrophysiology study proved that the F129I substitution in hERG1a significantly decreased IKr in both the homomeric and heteromeric hERG1channels by 86% and 70%, respectively (WT-hERG1a (54.88 ± 18.74) pA/pF vs. F129I-hERG1a (7.34 ± 1.90) pA/pF, P < 0.001; WT-hERG1a/hERG1b (89.92 ± 24.51) pA/pF vs. F129I-hERG1a/hERG1b (26.54 ± 9.83) pA/pF, P < 0.001). The voltage dependence of IKr activation (V½ and k) was not affected by the mutation in both the homomeric and heteromeric hERG1 channels. The peak current densities and the kinetic characteristics of IKr were comparable for both WT/F129I-hERG1a and WT-hERG1a. The channel inactivation and deactivation analysis showed that F129I substitution did not affect deactivation of the homomeric hERG1a channel, but significantly accelerated the deactivation and recovery from inactivation of the heteromeric hERG1a/hERG1b channel based on the time constants of fast and slow recovery from deactivation F129I-hERG1a/hERG1b vs. WT-hERG1a/hERG1b (P < 0.05). Western blotting and immunofluorescence labeling experiments showed that maturation and intracellular trafficking of the F129I-hERG1a protein was impaired and potentially increased the ratio of hERG1b to hERG1a in the F129I-hERG1a/hERG1b tetramer channel, thereby resulting in electrophysiological changes characteristic of the long QT syndrome type 2 pathology. Conclusions:. IKr was significantly reduced in the homomeric and heteromeric hERG1 channels with F129I-hERG1a. The F129I mutation significantly accelerated the deactivation and recovery from inactivation of the heteromeric F129I-hERG1a/hERG1b channel. F129I-hERG1a exhibited impaired maturation and intracellular trafficking, thereby potentially increasing the ratio of the hERG1b to hERG1a stoichiometry in the hERG1 tetrameric channel. These changes demonstrated the importance of the heteromeric hERG1 channel in long QT syndrome type 2 pathophysiology.